I don’t mind my information going to the Moon, but I don’t want any letters from Mars: a qualitative exploration of the challenges with secondary use of health data in Ireland - Tina Bedenik; Caitriona Cahir; Kathleen E. Bennett (Archives of Public Health, 2025)
Abstract Background Secondary use of health data is important for public and individual health due to its potential to drive research and healthcare improvement; however, there are challenges to be managed from a socio-ethical, legal and technological perspective. The aim of this qualitative study was to explore knowledge, experiences and perspectives of key stakeholders towards secondary use of health data in Ireland, with a specific focus on the challenges with secondary use. Methods The study employed a qualitative cross-sectional approach in accordance with the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Thirty-five people participated in the study, with seven participants in each of the five focus groups: academics and researchers; healthcare professionals; data controllers, ethics and privacy experts; industry group; and patients and public. Two thirds of the sample were female, and over half of participants were between 35 and 54 years of age. Participants were recruited through purposive and snowballing method. Data was collected through focus group discussions, transcribed and analysed thematically. Results The participants across all study groups were supportive of secondary use of health data; however, significant challenges were identified. The four main categories of challenges were related to (1) health data use, (2) ethics, (3) health data ecosystem and (4) social inequalities. Specifically, insufficient collection and low quality of health data, alongside issues regarding access, linking and sharing are a significant barrier to effective secondary use. This is further complicated by complex ethical approval processes and requirements around data protection. The fragmented national Information Technology (IT) and data infrastructure and limited resources further hamper secondary use, and concerns about low health literacy among the public and negative experiences with the healthcare system influence patients’ willingness to share data for secondary use. Conclusions This study identified the multi-layered and intersecting challenges in the Irish health data ecosystem around secondary use, and highlighted the need for structural improvements, reform of ethical processes, integration of disadvantaged communities, and education and awareness-raising among the public. A careful consideration of these challenges on a national level is required to enable effective secondary use of health data.